THEORETICAL AND PRACTICAL CONCERNS REGARDING THE CONCEPT OF COMPLEMENTARY PUNISHMENTS APPLICABLE TO NATURAL PEOPLE COMPLIANT TO THE REGULATIONS OF THE NEW CRIMINAL LAW - CRISTINA DANIELA MUNTEANU (Challenges of the Knowledge Society)
By this study we proposed to analyze the concept of complementary punishments applicable to natural people compliant to the regulations of the New Criminal Law, motivated by the numerous significant amendments brought in by the above mentioned writ, such as: deduction of the peak limits of the punishments from 10 to 5 years, increase of the number of the rights part of punishments’ content, significant increase of punishments’ field of incidence by introducing some of the safety orders into complementary punishments’ category (prohibition of entering certain cities, foreigners’ deporting, prohibition of returning to family’s residence for a certain period), the facility to advertise natural person’s Court Final Decision of sentencing, as well as many other news we intend to present in the present article.